2019
DOI: 10.1136/bmjopen-2019-033819
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bullying in the nursing workplace and determinant factors: a nationwide cross-sectional Polish study survey

Abstract: ObjectivesIn the present study, we aimed to investigate the prevalence of bullying among Polish nurses, and to identify the most common negative acts, as well as individual and work-related risk factors for workplace bullying.MethodsCross-sectional study designed using an online survey. The total study sample was 404 nurses, each having over 6 months of working experience. Data were collected using the Polish version of the Negative Act Questionnaire-Revised. Linear stepwise regression analysis and logistic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 36 publications
3
37
1
1
Order By: Relevance
“…This study found that younger workers were more likely to be bullied than senior ones. This finding was similar to results reported in Poland 58 and the UK, 15 but inconsistent with findings from Portugal 33 and Spain. 21 …”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This study found that younger workers were more likely to be bullied than senior ones. This finding was similar to results reported in Poland 58 and the UK, 15 but inconsistent with findings from Portugal 33 and Spain. 21 …”
Section: Discussionsupporting
confidence: 61%
“…Those with longer working hours are often susceptible to greater work overload, which can increase one’s sensitivity to bullying and increase exposure to violence and abuse. 58 , 60 , 61 This logical apprehension was reversed in the current study, noting that hospital workers in this study who worked <40 hours per week reported greater susceptibility to bullying than those who worked ≥40 hours per week. However, this can plausibly be explained through a string of observations via an anticipated triple-variable effect.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, no statistically significant associations were found between gender and any type of violence. Previous studies were not consistent in finding an association between gender and workplace violence [25][26][27]. However, female healthcare providers were found to have a higher risk of sexual harassment than their male counterparts [28].…”
Section: Discussionmentioning
confidence: 87%
“…Thus, about 65% of the nurses studied represent a group between 41–60 years of age, and nearly 85% are over 40 years old. Also, Serafin and Czarkowska‐Pączek (2019) observed that only 18.6% of nurses were aged below 29 years in their nationwide cross‐sectional Polish study survey. This trend is also observed in other counties around the world (Halcomb et al., 2018; Spiva et al., 2011).…”
Section: Discussionmentioning
confidence: 99%